2014
DOI: 10.1007/s40032-014-0159-4
|View full text |Cite
|
Sign up to set email alerts
|

Life Estimation of Hip Joint Prosthesis

Abstract: Hip joint is one of the largest weight-bearing structures in the human body. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…In a complete walking cycle, the hip joint rotates 80° [ 15 ]. The femoral head of the radius for this present study is 12 mm.…”
Section: Resultsmentioning
confidence: 99%
“…In a complete walking cycle, the hip joint rotates 80° [ 15 ]. The femoral head of the radius for this present study is 12 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have pointed out that although medical-grade titanium has excellent fatigue properties, the ISO pre-clinical durability testing standard does not adequately account for the influence of femoral offset or stem size to reflect safe design practice [26]. For static human body weight load, hip joint prostheses were found to be safe and dynamic analysis revealed that the hip joint prosthesis had an infinite fatigue life [27]. A hip joint model made of UHMWPE/ TiO2 Polymer composite used to study fatigue failure was found to be safe in static and fatigue analysis [23].…”
Section: Introductionmentioning
confidence: 99%